Apophyseal Ossification of the Iliac Crest in Forensic Age Estimation: Computed Tomography Standards for Modern Australian Subadults1. Issue 2 (25th November 2016) - Lottering, Nicolene; Alston‐Knox, Clair L.; MacGregor, Donna M.; Izatt, Maree T.; Grant, Caroline A.; Adam, Clayton J.; Gregory, Laura S.
Abstract: This study contrasts the ontogeny of the iliac crest apophysis using conventional radiography and multislice computed tomography (MSCT), providing probabilistic information for age estimation of modern Australian subadults. Retrospective abdominopelvic MSCT data acquired from 524 Australian individuals aged 7–25 and surveillance radiographs of adolescent idiopathic scoliosis patients included in the Paediatric Spine Research Group Progression Study ( n = 531) were assessed. Ossification scoring of pseudo‐radiographs and three‐dimensional (3D) volume‐rendered reconstructions using Risser (1958) quantitative descriptors indicate discrepancies in age estimates, stage allocation, and conflicting morphological progression. To mitigate visualization limitations associated with two‐dimensional radiographs, we provide and validate a modified 3D‐MSCT scoring tier of ossification, demonstrating complete fusion between 17.3–19.2 and 17.1–20.1 years in males and females. Legal demarcation for doli incapax presumption and age of majority (18 years) can be achieved using probability estimates from a fitted cumulative probit model for apophyseal fusion using the recalibrated standards.